2002
DOI: 10.1177/10983007020040030301
|View full text |Cite
|
Sign up to set email alerts
|

Employing Descriptive Functional Assessment Methods to Assess Low-Rate, High-Intensity Behaviors

Abstract: Low-rate, high-intensity behaviors, such as aggression and violence, are not uncommon in school settings. This study evaluated the utility of descriptive methods (e.g., record reviews, interviews) of functional assessment in documenting behavior function for low-rate, high-intensity behaviors. The participant, a 13-year-old boy with ADHD, exhibited low rates of aggression toward peers in school. A comprehensive record review of archival data sources (i.e., office referrals, previous school records) indicated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…It may also be used on parent/teacher/staff to evaluate the current contingencies that NARRATIVE AND STRUCTURED ABC FORMS 21 maintain their responding to the problem behavior, thereby providing some information of whether or not the environment support problematic behavior (Penche, et al, 2009). It may also be more suitable for situations where problematic behavior occurs at a low rate such that EFA may not observe differentiated levels of responding because of insufficient levels of responding (e.g., Radford & Ervin, 2002). Lastly it may guide the design of an EFA by identifying what conditions are unlikely to support problematic behavior and excluding them from further analysis The most prevalent limitation to descriptive assessments is that the data is purely correlational and prone to several errors as such.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be used on parent/teacher/staff to evaluate the current contingencies that NARRATIVE AND STRUCTURED ABC FORMS 21 maintain their responding to the problem behavior, thereby providing some information of whether or not the environment support problematic behavior (Penche, et al, 2009). It may also be more suitable for situations where problematic behavior occurs at a low rate such that EFA may not observe differentiated levels of responding because of insufficient levels of responding (e.g., Radford & Ervin, 2002). Lastly it may guide the design of an EFA by identifying what conditions are unlikely to support problematic behavior and excluding them from further analysis The most prevalent limitation to descriptive assessments is that the data is purely correlational and prone to several errors as such.…”
Section: Discussionmentioning
confidence: 99%
“…A full reading of IDEA indicates that preventive interventions are preferred, such as early intervention and IEPs that include positive behavior support when needed. A case example of a functional assessment of a dangerous, low-rate, high-intensity behavior (severe physical aggression) was described by Radford and Ervin (2002). In this case, a review of records and direct observations indicated that IDEA 2004: The Reauthorized FBA 13 the physical aggression was related to verbal aggression (e.g., swearing, name-calling).…”
Section: Misconduct Involves Weapons Drugs or Serious Bodily Injury:mentioning
confidence: 96%
“…Well-supported hypotheses serve as the foundation for intervention (Radford & Ervin, 2002;Umbreit et al, 2004). The methods selected respond explicitly to patterns identified via the FBA and are multicomponent in nature.…”
Section: Fba Process and Toolsmentioning
confidence: 99%
“…A number of studies conducted in the early 1990s demonstrated the effectiveness of functional analysis and PBS procedures with students described as having EBS (e.g., Clarke et al, 1995;Kern et al, 1994;Lane, Umbreit, & Beebe-Frankenberger, 1999). Other studies extended the use of PBS to individuals without identified disabilities (e.g., Lewis, Powers, Kelk, & Newcomer, 2002;Umbreit, Lane, & Dejud, 2004) and to other contexts, including general education settings (e.g., Radford & Ervin, 2002;Scott, 2001;. The expansion and growing acceptance of PBS is illustrated in language in the IDEA reauthorization (Skiba, Bear, & Browning Wright, 2004) encouraging the use of FBA and positive supports and strategies for students with disabilities experiencing behavioral challenges.…”
mentioning
confidence: 96%